PENERAPAN BALANCED SCORECARD DALAM MENINGKATKAN KINERJA PERUSAHAAN - Suhaya, Mr (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
The purpose of this study was to determine the effect of financial perspective, customer perspective, internal business processes also learning and growth perspective on the company performance either partially or simultaneously of PT. JJ-LAPP CABLE SMI - Tangerang. The research method uses quantitative, analysis uses regression, explanation uses descriptive, and discussion uses verification. The object of research is PT. JJ-Lapp Cable SMI, sampling technique using simple random sampling, and data collection techniques using questionnaires. The results showed the dimensions of the balance score card affect business effectiveness, therefore it is important for companies to improve internal conditions and increase strength to deal with external threats.